1992
DOI: 10.1212/wnl.42.7.1291
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and structural brain lesions in multiple sclerosis

Abstract: Quantified lesion scores derived from MRI correlate significantly with neuropsychological testing in patients with multiple sclerosis (MS). Variables used to reflect disease severity include total lesion area (TLA), ventricular-brain ratio, and size of the corpus callosum. We used these general measures of cerebral lesion involvement as well as specific ratings of lesion involvement by frontal, temporal, and parieto-occipital regions to quantify the topographic distribution of lesions and consequent effects up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
90
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(97 citation statements)
references
References 0 publications
4
90
0
3
Order By: Relevance
“…The presence of widespread lesions leads to the disruption of WM pathways, which connect distant brain regions involved in the complex processes required to perform PASAT correctly. In most of the previous studies, correlations between T2-W LV and NP performance have been weak or moderate (Foong et al, 1997;Rao et al, 1989;Rovaris et al, 2002;Swirsky-Sacchetti et al, 1992). This is most likely owing to the poor pathological specificity of the abnormalities detected on T2-W scans and to the inability of conventional MRI to assess the extent of subtle changes in the normal-appearing brain tissue.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of widespread lesions leads to the disruption of WM pathways, which connect distant brain regions involved in the complex processes required to perform PASAT correctly. In most of the previous studies, correlations between T2-W LV and NP performance have been weak or moderate (Foong et al, 1997;Rao et al, 1989;Rovaris et al, 2002;Swirsky-Sacchetti et al, 1992). This is most likely owing to the poor pathological specificity of the abnormalities detected on T2-W scans and to the inability of conventional MRI to assess the extent of subtle changes in the normal-appearing brain tissue.…”
Section: Discussionmentioning
confidence: 97%
“…Swirsky-Sacchetti et al 8 found that left frontal lesion area predicted perseverative responses on the Wisconsin Card Sorting Test (WCST). Although the authors did not control for total lesion load, Arnett et al 1 controlled for this factor by dividing patients into those with and without predominantly frontal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…t is well established that MS-associated cognitive impairment is associated with general MRI measures of disease burden such as the total area or volume of T 2 lesions (TLA), [1][2][3][4][5][6][7][8] cerebral volume, 2,7,9 corpus callosum size, 5,7,10 and third ventricle volume or width (3VW). 5,11,12 In contrast, correlations between region-specific pathology on MRI and specific cognitive deficits are rarely reported.…”
mentioning
confidence: 99%
“…Increasing recognition of the functional relevance and prognostic role of MS cognitive impairments has resulted in focused attention on MR correlates of cognitive deficit. Assessment of the global and regional white matter (WM) lesion burden, derived from T2-or T1-weighted MRI shows modest association with cognitive status (Arnett et al, 1994;Hohol, et al, 1997;Patti et al, 2009;Rao et al, 1989;Rovaris et al, 2001;Swirsky-Sacchetti et al, 1992). A stronger relationship has been obtained with quantification of the whole and…”
Section: Introductionmentioning
confidence: 99%